PENGARUH SENAM POCO-POCO TERHADAP KADAR KOLESTEROL LOW DENSITY LIPOPROTEIN DARAH - Saputra, Asep D.; Ticoalu, Shane H. R.; Wongkar, Djon (eBiomedik, 2015)
Abstract: High level of plasma LDL-cholesterol concentrations is one of the cause of atherosclerosis that may result in cardiovascular diseases (CVD), such as coronary heart disease (CHD) and stroke. Exercise can improve plasma LDL-cholesterol concentrations. A type of exercise, poco-poco, is categorized to the aerobic gymnastics. This study aimed to know the influence of poco-poco to plasma LDL-cholesterol concentrations. This was an experimental study with one group prestest-posttest design. Samples were 25 female students of 2013 batch Pharmacy study program of Sam Ratulangi University Manado that were chosen with purposive sampling. Samples did poco-poco gymnasticss three times a week for four consecutive weeks. The results showed that after four weeks of poco-poco there was an increase of the average of plasma LDL-cholesterol concentrations for 1.120 mg/dl, but this increase was not statistically significant (p > 0.05). Conclusion: There was no significant influence of doing poco-poco for four weeks to plasma LDL-cholesterol concentrations.Keywords: poco-poco gymnastics, low density lipoproteinAbstrak: Tingginya kadar kolesterol-LDL darah merupakan penyebab utama terjadinya aterosklerosis yang berujung pada munculnya penyakit kardiovaskular (PKV), seperti penyakit jantung koroner (PJK) dan stroke. Olahraga merupakan salah satu cara yang bisa digunakan untuk memperbaiki kadar kolesterol-LDL darah. Senam poco-poco termasuk dalam olah raga dengan kategori senam aerobik. Penelitian ini bertujuan untuk mengetahui pengaruh senam poco-poco terhadap kadar kolesterol-LDL darah. Penelitian ini bersifat eksperimental dengan desain one group prestest-posttest. Sampel penelitian ialah mahasiswa Fakultas MIPA Program Studi Farmasi Universitas Sam Ratulangi Manado Angkatan 2013 sebanyak 25 orang yang dipilih secara purposive sampling. Sampel melakukan senam poco-poco sebanyak tiga kali dalam seminggu selama empat minggu. Hasil penelitian memperlihatkan bahwa setelah melakukan senam poco-poco selama empat minggu terjadi peningkatan rata-rata kadar kolesterol-LDL darah sebanyak 1,120 mg/dl, namun perubahan ini tidak bermakna secara statistik (p > 0,05). Simpulan: Tidak terdapat perubahan yang bermakna secara statistik terhadap kadar kolesterol-LDL darah setelah melakukan senam poco-poco selama empat mingguKata kunci: senam poco-poco, low density lipoprotein